Low energy loss (0.42 eV) and efficiency over 15% enabled by non-fullerene acceptors containing N-bis(trifluoromethyl)phenylbenzotriazole as the core in binary solar cells. Issue 36 (30th August 2022) - Privado, María; Donoso, Beatriz; Khandelwal, Kanupriya; Singhal, Rahul; Guijarro, Fernando G.; Díaz-Ortíz, Ángel; Prieto, Pilar; de la Cruz, Pilar; Sharma, Ganesh D.; Langa, Fernando
Abstract : Binary OSCs with an efficiency as high as 15.17% are prepared using a new acceptor with a 3, 5-bis(trifluoromethyl)phenyl as the N-substituent in a benzotriazole core and a donor polymer. Abstract : Two non-fullerene acceptors, A–D–A′–D–A systems, with an identical central 2-(3, 5-bis(trifluoromethyl)phenyl)-2 H -benzo[ d ][1, 2, 3]triazole (CF3 -BTA) (A′) connected with 4, 4-bis (2-ethylhexyl)-4 H -cyclopenta[[2, 1- b ]3, 4- b ′]dithiophene (CPDT) (D), to different end capped acceptor units, namely tricyanoethylene (TOCR1 ) and 2-(5, 6-difluoro-3-oxo-2, 3-dihydro-1 H -inden-1-yldene)malononitrile (TOCR2 ) are prepared. These two materials were used as acceptors in polymer solar cells, along with two wide band-gap conjugated polymers, P1 or P2. Following optimization of the weight ratio variation and solvent vapor annealing process, the PSCs based on P1:TOCR1, P1:TOCR2, P2:TOCR1 and P2:TOCR2 demonstrated overall power conversion efficiency (PCE) of 10.31, 15.17, 11.88, and 5.89 percent with the highest value corresponding to P1:TOCR2 (15.17%). The high value of exciton dissociation and charge collection probability in P1:TOCR2 may explain the high PCE value. The lowest value of P2:TOCR2 based PSCs, on the other hand, is due to the low HOMO offset between TOCR2 and P2, which hinders exciton dissociation and hole transfer from TOCR2 to P2, as evidenced by the fact that the photoluminescence intensity of pristine TOCR2 is not fully quenched in the P2:TOCR2 blend, whereas the PL intensity of TOCR1 or TOCR2 is completely quenched in P1:TOCR1, P1:TOCR2 and P2:TOCR1 blends.